2020
DOI: 10.1088/1742-6596/1342/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

The KDK (potassium decay) experiment

Abstract: Potassium-40 (40K) is a background in many rare-event searches and may well play a role in interpreting results from the DAMA dark-matter search. The electron-capture decay of 40K to the ground state of 40 Ar has never been measured and contributes an unknown amount of background. The KDK (potassium decay) collaboration will measure this branching ratio using a 40K source, an X-ray detector, and the Modular Total Absorption Spectrometer at Oak Ridge National Laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…where x is the shell, n x is the relative occupation number, C x contains the dependence of electron capture rates on nu-clear structure giving the forbiddenness classification, similar to the shape factor in β decay (Emery, 1975), f x is the integrated fermi function in β decay, f β + is the integrated positron spectrum, and C(W ) is the theoretical shape factor for allowed or forbidden transitions. A review of shape factors for 40 K transitions is provided by Cresswell et al (2018Cresswell et al ( , 2019.…”
Section: Theory and Calculation Of Ec Ground /β +mentioning
confidence: 99%
See 1 more Smart Citation
“…where x is the shell, n x is the relative occupation number, C x contains the dependence of electron capture rates on nu-clear structure giving the forbiddenness classification, similar to the shape factor in β decay (Emery, 1975), f x is the integrated fermi function in β decay, f β + is the integrated positron spectrum, and C(W ) is the theoretical shape factor for allowed or forbidden transitions. A review of shape factors for 40 K transitions is provided by Cresswell et al (2018Cresswell et al ( , 2019.…”
Section: Theory and Calculation Of Ec Ground /β +mentioning
confidence: 99%
“…Unlike 40 K, the dominant decay of 22 Na is the β + decay mode. This is due to the greater difference in energy between the initial and final states, as positron decay will have a greater possibility of occurring in decays with a greater mass differences between initial and final states (Emery, 1975). 22 Na is not a perfect analogue; however, it is probably the best choice that 2010and Leutz et al (1965).…”
Section: Comparison With 22 Namentioning
confidence: 99%
“…In the case of 40 K, verification of the EC ground decay can be achieved by measuring the characteristic x-rays (Di Stefano et al, 2017). The orbital electron with the highest probability of capture is from the K-shell; if this electron is captured, it results in https://doi.org/10.5194/gchron-2020-9 Preprint.…”
Section: Experimental Verification Of Ec Ground Decay Modementioning
confidence: 99%
“…However, electron capture to both the ground and excited state of 40 Ar ( 40 Ar 2+) result in the same electron configuration and x-ray emissions. Di Stefano et al (2017) suggested tagging x-rays with the de-excitation γ associated with electron capture to 40 Ar 2+ , which has a lifetime on the order of ~ 10 -12 s (Di Stefano et al, 2017). X-rays tagged by the 1.46 MeV γ must correspond to electron capture to the excited 40 Ar 2+ state, with those x-rays not tagged correspond to the the electron capture to ground state decay.…”
Section: Experimental Verification Of Ec Ground Decay Modementioning
confidence: 99%
See 1 more Smart Citation